Analisa Kromatografi Gas Spektrometri Massa dan Gugus Fungsi Ekstrak Metanol Daun Bidara (Ziziphus mauritiana): Analisa Kromatografi Gas Spektrometri Massa dan Gugus Fungsi Ekstrak Metanol Daun Bidara (Ziziphus mauritiana) - Widiarti, Leni; Febriani, Husnarika; Dur, Sajaratud; Ningrum, Nurlian Augustin; Nurcahyani, Nadya; Andry, Muhammad (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Bidara leaves are a plant that is quite abundant in Medan and has many benefits in the health sector. The aim of this research is to predict the content of secondary metabolite compounds in bidara leaf extract, through qualitative tests by screening using specific reagents, functional group analysis with FT-IR and mass analysis with GC-MS. The screening results showed that the methanol extract of bidara leaves contained alkaloids, flavonoids, tannins, saponins and phenols. Functional group analysis shows that the wavelength area is 3300 cm-1, namely OH absorption, 2700 - 2900 cm-1 shows C-H absorption, 1600 - 1700 cm-1 shows C=O absorption, 1400 - 1450 cm-1 shows C-H absorption, 1365 - 1385 cm-1 shows CH3 bent absorption, and 1000 – 1100 cm-1 shows C-O absorption. The results of mass analysis using GC-MS showed four dominant peaks from the compound, namely Z-5-Methyl-6-heneicosen-11-one, 17-Pentatriacontene, Ethyl iso-allocholate and Pentacosane.